Urbanization, Natural Amenities, and Subjective Well-Being: Evidence from U.S. Counties - John V. Winters; Yu Li (Institute for the Study of Labor (IZA), 2015)
This paper examines the effects of county-level urbanization and natural amenities on subjective well-being (SWB) in the U.S. SWB is measured using individual-level data from the Behavioral Risk Factor Surveillance System (BRFSS) which asks respondents to rate their overall life satisfaction. Using individual-level SWB data allows us to control for several important individual characteristics. The results suggest that urbanization lowers SWB, with relatively large negative effects for residents in dense counties and large metropolitan areas. Natural amenities also affect SWB, with warmer winters having a significant positive effect on self-reported life-satisfaction. Implications for researchers and policymakers are discussed.
Keywords: I00; Q00; R00; 330; subjective well-being; urbanization; population density; amenities; quality of life